2001
DOI: 10.1002/1438-5171(200112)2:4<241::aid-simo241>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Original Tools for Single-Molecule Spectroscopy

Abstract: Characterizing individually nanoparticles or probing complex environments by single molecule can be a powerful approach provided that spectroscopic techniques, tailored to such systems, have been developed to extract pertinent physico-chemical parameters of interest. In the paper, we report on two techniques that were missing in SingleMolecule Spectroscopy (SMS) toolbox. The first concerns polarization. Due to molecule anisotropy, 3D-molecular orientation is a well-defined parameter. In principle, SMS can take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the growing field of single-molecule spectroscopy, there has been considerable recent interest in optical probes for nanoscale orientation sensing. The currently employed technique is based on measuring the polarization of anisotropic fluorescent probes [1][2][3][4][5][6][7][8][9][10] or the lateral position of micrometer-sized beads. 11,12 Local orientation sensors are important in material research, e.g., the study of liquids in confined spaces, 13 liquid crystal orientation, 14 and the structure of glasses and polymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the growing field of single-molecule spectroscopy, there has been considerable recent interest in optical probes for nanoscale orientation sensing. The currently employed technique is based on measuring the polarization of anisotropic fluorescent probes [1][2][3][4][5][6][7][8][9][10] or the lateral position of micrometer-sized beads. 11,12 Local orientation sensors are important in material research, e.g., the study of liquids in confined spaces, 13 liquid crystal orientation, 14 and the structure of glasses and polymers.…”
mentioning
confidence: 99%
“…In the growing field of single-molecule spectroscopy, there has been considerable recent interest in optical probes for nanoscale orientation sensing. The currently employed technique is based on measuring the polarization of anisotropic fluorescent probes or the lateral position of micrometer-sized beads. , Local orientation sensors are important in material research, e.g., the study of liquids in confined spaces, liquid crystal orientation, and the structure of glasses and polymers . In biomolecular research, monitoring orientation changes and rotations of biomolecules during their functional task have explained the mechanism of molecular motors , and helped to explain the mechanical properties of DNA …”
mentioning
confidence: 99%
“…This can be achieved in different ways in wide-field imaging approaches using TIR and taking advantage of aberrations induced by index mismatch in high numerical aperture objectives [85], defocalization effects [86] or excitation with alternating polarizations [82]. Other approaches using confocal scheme and using amplitude [87] or phase masks [88] allow a complete determination of this orientation. In the case of a planar degenerate transition dipole as exhibited by nanocrystals or some highly symmetric molecules, a simpler approach using variable polarization excitation provides the 3-dimensional orientation of the molecule [48].…”
Section: Fluorescence Polarizationmentioning
confidence: 99%
“…What's more, Novotny et al have demonstrated that orientations of single molecules are efficiently mapped out in three dimensions by using a radially polarized beam as the excitation source [14]. And the radially polarized beams have been used for optimizing photon collection efficiency of molecular-based single-photon sources [15,16], acceleration techniques [17]. Because of the special properties of the radially polarized beams, they can be used in guiding or trapping the particles [18,19] and scanning the optical microscopy [20].…”
Section: Introductionmentioning
confidence: 99%